Influence of United States Constitutional System on Asian Countries - Mendy, Ousu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
United States of America is a leading superpower in international politics and the infiltration of its constitutional system into other countries is quite conspicuous in many ways. The impact of it is manifest in the governance structure many Asian countries. Asia is an abode to different types of governments including long-established democracy, socialism and monarchies. This research studies and compares special Asian countries with the constitutional system of America as a model that has withstood the test to time since the 18th century. This research finds that the question of whether Asia can adopt democracy was what preoccupied Lee Kuan Yew as an Asian and Singaporean statesman. However, diffusion theory penetrates Asia, and the continent begins to wax in democracy and constitutionalism. Written constitutions also dominate Asia with models of check and balance, impeachments, and elimination of dictatorship although its last vestiges are still in some parts of the continent.